Mureinolytic ability of the rumen ciliate Diploplastron affine - Bełżecki, G; Miltko, R; Kwiatkowska, E; Michałowski, T (Folia microbiologica, 2010)
Rumen ciliate protozoa intensively engulf bacteria. However, their ability to utilize murein which is the main polysaccharide of bacterial cell wall has hardly been recognized. The present study concerns the ability of the rumen protozoa Diploplastron affine to digest and ferment murein. The ciliates were isolated from the rumen fluid and grown in vitro or inoculated into the rumen of defaunated sheep. The results of long-term cultivation of protozoa showed a positive correlation between their number and murein content in the culture medium. It was also found that bacteria-free D. affine ciliates incubated with or without murein produced volatile fatty acids at the rate of 12.3 and 8.7 pmol/h per protozoan, respectively, acetic, butyric and propionic acids being the three main acids released to the medium. Enzyme studies performed with the use of protozoan cell extract prepared from bacteria-free ciliates degraded murein at a rate of 25 U/mg protein per h; two mureinolytic enzymes were identified by zymographic technique in the examined preparation.
Keywords: bachor; kultivační média; Fatty Acids, Volatile; ovce; Animals; Financing, Organized; financování organizované; Rumen; kyseliny mastné těkavé; Culture Media; zvířata; Ciliophora; Peptidoglycan; peptidoglykan; Sheep